Screening for phytochemical constituents and antioxidant activity of flower extracts of Quisqualis indica linn / Suhaidi Ariffin and Nurul Izzah Radin Mokthar - Ariffin, Suhaidi; Radin Mokthar, Nurul Izzah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Rangoon creeper, scientifically known as Quisqualis indica Linn. belongs to the family of Combretaceae and has been used as a traditional medicine for a long time. This plant treats many illnesses, such as fever and boil, and relieves headaches. However, the scientific data to support the effectiveness of this plant as a medicinal source still needs to be discovered. Therefore, this study aims to identify phytochemical constituents and determine the antioxidant properties of flower extracts of Q. indica L. Maceration technique was employed to extract the sample using three different solvent polarities: n-hexane, ethyl acetate, and methanol. The extractive yield of methanol showed the highest percentage, 17.41%, followed by ethyl acetate (3.19%) and n-hexane (1.45%), respectively. For phytochemicals screening, all extracts exhibited the presence of alkaloids, flavonoids, saponins, terpenoids, and tannins, except the n-hexane extract, where flavonoids are not detected. The antioxidant assay was done by DPPH (2,2 diphenyl-1-picrylhydrazyl) assay at 1000 μg/mL concentration. It was found that the methanol extract gave the highest DPPH radical scavenging activity of 99.11 ± 0.50%, which is higher than the ascorbic acid standard used. The results justify its use as a medicinal plant. This local species has a higher potential as an antioxidant agent as well.